Pengaruh Pelayanan Cleaning Service dan Keterbatasan Bahan Baku Permakanan yang Dilaksanakan Oleh PT. Pelita Indonesia Djaya Terhadap Kepuasan Penumpang Kapal PT. PELNI - Siti Nurjanah; Achsanul Nashir (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. PT. Pelita Indonesia Djaya handles imports and exports, and plays a vital role in meeting the needs of ship passengers through the provision of food supplies and cleaning services. The purpose of this study is to analyze the influence of cleaning service and the availability of food supplies on passenger satisfaction on PELNI ships. Quantitative methods were used to evaluate the influence of cleaning service and the availability of supplies on passenger satisfaction. Using the Slovin formula, the research sample consisted of 98 people. The results indicate that cleaning service and availability of supplies on passenger satisfaction. The availability of food supplies and cleaning services simultaneously have a positive and significant impact on passenger satisfaction. According to the multiple linear regression analysis, the combination of these variables contributes to passenger satisfaction. The results show that improving service quality and raw material availability is very important to increase passenger satisfaction. Keywords: Availability, Passenger Satisfaction, Service